The Birth and Rise of Universiti Sains Malaysia (USM) - Some Ruminations - Fazal, Anwar (2019)
This is a broad sweep of the story of the U niversiti Sa ins Malaysia (USM) in multi verse Penang. It shares l:he unusual institutions and individuals that made Penang an intellectual hub and how this new unique instirution sprouted out to be a centtre of excellence and innovation in higher education in Malaysia and globally. I share my own journey with USM and some of the unusual stories and initiatives that I was associated with. I add my own thoughts on what made USM a shining star both locally and globally.